2018
DOI: 10.1183/16000617.0061-2018
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mortality and mortality rates in interstitial lung disease patients in the intensive care unit

Abstract: Data on interstitial lung disease (ILD) outcomes in the intensive care unit (ICU) is of limited value due to population heterogeneity. The aim of this study was to examine risk factors for mortality and ILD mortality rates in the ICU.We performed a systematic review using five databases. 50 studies were identified and 34 were included: 17 studies on various aetiologies of ILD (mixed-ILD) and 17 on idiopathic pulmonary fibrosis (IPF). In mixed-ILD, elevated APACHE score, hypoxaemia and mechanical ventilation ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 55 publications
2
33
2
Order By: Relevance
“…A systematic review of ILD patients treated in intensive care units without ECMO showed that mortality was 65% in patients with idiopathic pulmonary brosis during the period 2005-2017 and 48% in mixed ILD patients between 2010 and 2017 (2). In our study, the rate of in-hospital mortality (74.4%) in mixed ILD patients treated with ECMO turned out to be higher than previously reported mortality rates among patients receiving conventional treatments without ECMO.…”
Section: Discussioncontrasting
confidence: 60%
“…A systematic review of ILD patients treated in intensive care units without ECMO showed that mortality was 65% in patients with idiopathic pulmonary brosis during the period 2005-2017 and 48% in mixed ILD patients between 2010 and 2017 (2). In our study, the rate of in-hospital mortality (74.4%) in mixed ILD patients treated with ECMO turned out to be higher than previously reported mortality rates among patients receiving conventional treatments without ECMO.…”
Section: Discussioncontrasting
confidence: 60%
“…Collagen Tissue Disease–associated Interstitial Lung Fibrosis (CTD-ILDs) and Bronchiolitis Obliterans Syndrome (BOS) represent two severe lung fibrogenic disorders involving, respectively, the lung interstitium and small airways, which share several pathogenic mechanisms and a poor long term outcome [1,2]. Common pathogenic steps include injury of airway epithelium due to immune-inflammatory insults, followed by a trigger of alveolar and bronchiolar epithelial cells transition towards myofibroblasts (epithelial mesenchymal transition, EMT) and a fibro-proliferative phase with uncontrolled extracellular matrix (ECM) deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Improving outcomes in interstitial lung disease patients mechanically ventilated in the ICU Alexandre Demoule focused on outcomes and treatment strategies for interstitial lung disease (ILD) patients in the ICU. "We can only improve" was the take home message as the mortality of ILD patients exceeds 50% [97], with mechanical ventilation as a primary risk factor [98]. NIV and HFNC are scarcely explored and should not delay intubation.…”
Section: Modulation Of Drive: Ecco 2 Rmentioning
confidence: 99%